2023
DOI: 10.1038/s41598-023-30941-0
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid deep learning approach for COVID-19 detection based on genomic image processing techniques

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has been spreading quickly, threatening the public health system. Consequently, positive COVID-19 cases must be rapidly detected and treated. Automatic detection systems are essential for controlling the COVID-19 pandemic. Molecular techniques and medical imaging scans are among the most effective approaches for detecting COVID-19. Although these approaches are crucial for controlling the COVID-19 pandemic, they have certain limitations. This study proposes an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…To create useful systems that can detect COVID-19, these signals were analyzed using digital signal processing technologies. In another study, COVID-19 was identified using genomic image-processing (GIP) methods 44 . GIP is an area of bioinformatics that connects bioinformatics with image processing techniques.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To create useful systems that can detect COVID-19, these signals were analyzed using digital signal processing technologies. In another study, COVID-19 was identified using genomic image-processing (GIP) methods 44 . GIP is an area of bioinformatics that connects bioinformatics with image processing techniques.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hybrid models combining techniques like Sparger Wolf Hawk Optimization with deep neural networks have also shown promise for COVID-19 assessment (10) . For text data, weighting schemes have been employed to extract informative features from clinical notes for COVID-19 identification and mortality prediction (11) . Deep learning methods have effectively utilized both image and text data, proving superior to classical machine learning techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The most recent work on covid-19 can be found in the work of 29 , where they have determined spread of infection rate using superposition rule of Gaussian pulses and informed the world by elaborating the occurrence of multiple waves. The speed rate of this disease was high, that is why, Hammad et al 30 implemented a technique, based on image processing, for the fast detection of covid disease and its controlling. In 2021, Paul et al 31 worked on the fast emergence of covid by introducing two parameters-based model, while Photiou 32 gathered data from the social media and informed the world about the spread of this pandemic disease.…”
Section: Introductionmentioning
confidence: 99%